Symbolism in Poe's "The Haunted Palace" - Kuhon, Fiola (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2018)
ABSTRACTPoetry always has a unique charm that captivates and draws the reader into its figurative world. One of the most interesting charm is symbolism used by the poet, in one single word lays a deeper explanation beyond what is perceptible by the eyes. Therefore, the aim of this research was to reveal the symbolism in “The Haunted Palace”, a gothic-themed poetry written by a well-known poet Sir Edgar Allan Poe. Having analyzed this poetry, the writer later found that Poe’s “The Haunted Palace” has some unique symbols used by the poet himself. Despite of writing long and descriptive lines, the poet chose appropriate symbols that lead the readers to think and conjecturing more deeply. Every symbol used in “The Haunted Palace” represents simplicity, authenticity and brilliancy of Poe himself. Thus, a symbolism holds a very important role of poetry. It is not only pleasantly presented but also elucidating things beyond its literal substance. It proves that Poe’s “The Haunted Palace” is pleasant to be read but difficult to be interpreted.Keywords: poetry, symbolism, The Haunted Palace, Edgar Allan Poe